Optimal sizing of a solar water pumping system for Koyli Alpha Village, Senegal - Badara Mbow; Amy Sadio; Bertrand Tchanche Fankam; Senghane Mbodji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Our objective is to solve problems of water supply in the village of Koyli Alpha, in Senegal. Theirs boreholes are supplied by diesel fuels causing environmental drawbacks and the populations don’t satisfy their water demand. In order to bring a positive response, we used solar energy to give back the borehole’s autonomous and proposed intuitive and numerical methods applying on solar water pumping for finding the best method. A previous study used intuitive methods for determining the size of various components. In order to optimize the energy production, we propose two numerical sizing approaches in order to have an optimal operation. Then, we developed two solar cell temperature models in the numerical sizing method and did a simulation of system operating in MATLAB software. The first model of solar cell temperature depends only on the ambient temperature and the second one combines wind speed and ambient temperature. The results of simulation showed that among these numerical sizing methods, we choose the second solar cell temperature expression, which gives the best performance. The numerical sizing method which uses the second solar cell temperature model yields to the reduction of battery’s size and the total life cycle cost found in the intuitive method, by 54% and 32%, respectively.